Radical Radiotherapy for High-Risk Prostate Cancer in Older Men - Payne, Heather A. (AlphaMed Press, 2012)
Historical data for older men with high-risk nonmetastatic prostate cancer treated with radiotherapy alone have demonstrated a 10-year prostate-cancer-specific mortality of around 30%. The development of dose escalation, using techniques such as intensity-modulated radiotherapy, has enabled more targeted delivery of treatment with improved efficacy and a reduction in the risk of toxicity compared with conventional radiotherapy. The combination of radiotherapy and androgen-deprivation therapy (ADT) has been shown to improve overall survival compared with radiotherapy or ADT alone without a significant increase in toxicity in patients with minimal comorbidities. There is evidence that patient age has only a marginal effect on genitourinary and gastrointestinal toxicities following radiotherapy. Further research has shown that although age does have an effect on the likelihood of sexual dysfunction after radiation therapy, there is no significant difference in the proportion of men aged ≥75 years who feel that sexual dysfunction is a moderate or serious problem before or 24 months after diagnosis. Radical radiotherapy is effective and well tolerated in senior men with high-risk prostate cancer and should be offered in combination with long-term ADT to patients with minimal comorbidities. In case of significant comorbid conditions, shorter durations of ADT may be considered.